2020
DOI: 10.1001/jamadermatol.2020.0035
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Effectiveness and Tolerability of Mycophenolate Mofetil and Mycophenolic Acid for the Treatment of Morphea

Abstract: IMPORTANCEFirst-line systemic therapy for morphea includes methotrexate with or without systemic corticosteroids. When this regimen is ineffective, not tolerated, or contraindicated, a trial of mycophenolate mofetil (MMF) or mycophenolic acid (MPA)-referred to herein as mycophenolate-is recommended; however, evidence to support this recommendation remains weak.OBJECTIVE To evaluate the effectiveness and tolerability of mycophenolate for the treatment of morphea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…There is a potential role for hydroxychloroquine in the treatment of morphea, with a retrospective study showing a majority of patients having at least a greater than 50% response to 6 months of therapy 7 . A retrospective study of mycophenolate in the treatment of morphea showed a majority of patients to have stable or improved disease within 3–6 months of therapy 8 . However, further studies are needed to better elucidate the efficacy of these therapies in radiation‐induced morphea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a potential role for hydroxychloroquine in the treatment of morphea, with a retrospective study showing a majority of patients having at least a greater than 50% response to 6 months of therapy 7 . A retrospective study of mycophenolate in the treatment of morphea showed a majority of patients to have stable or improved disease within 3–6 months of therapy 8 . However, further studies are needed to better elucidate the efficacy of these therapies in radiation‐induced morphea.…”
Section: Discussionmentioning
confidence: 99%
“…7 A retrospective study of mycophenolate in the treatment of morphea showed a majority of patients to have stable or improved disease within 3-6 months of therapy. 8 However, further studies are needed to better elucidate the efficacy of these therapies in radiation-induced morphea. Familiarity with this condition as sequelae of radiation therapy can lead to earlier recognition and dermatologic referral, improving the outcomes and quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of MMF in 22 patients with JLS compared to 47 on MTX showed no significant difference in relapse-free survival between the groups although MMF appeared to induce more persistent remission, and MMF was well tolerated 40 . In a study of 77 participants (all 16 years or older), MMF was well tolerated with 35% achieving disease remission 52 . Both studies concluded that further controlled studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by three retrospective cohort studies with a total of 94 patients who received second‐line MMF therapy, usually concomitant with additional treatment 24–26 . Of the patients with a treatment duration of at least 9 months, 25% had stable and 61% had improved disease 24 . However, cases refractory to MMF have been observed, and the treatment of recalcitrant morphoea remains largely empirical.…”
Section: Second‐line Therapy For Difficult‐to‐treat Casesmentioning
confidence: 91%